Controlled synthesis of Ru-single-atoms on ordered mesoporous phosphine polymers for microwave-assisted conversion of biomass-derived sugars to artificial sweeteners. Issue 42 (20th October 2022) - Modak, Arindam; Gill, Deepika; Mankar, Akshay R.; Pant, Kamal K.; Bhasin, Vidha; Nayak, Chandrani; Bhattacharya, Saswata
Abstract : Ru-single-atoms in ordered mesoporous phosphine polymers as microwave-assisted selective transfer hydrogenation catalysts for the conversion of biomass-derived xylose and glucose to sugar alcohols. Abstract : Atomically dispersed metal-single-atoms have become a frontier in solid catalysis due to their characteristic electronic properties. However, for biomass conversion, employing metal-single-atoms as catalysts is rather challenging since they suffer from poor selectivity and yield due to inadequate metal–support interactions. We show here that Ru/triphenylphosphine (PPh)-based ordered mesoporous polymers afford high yields of reduced sugars, xylitol (yield ∼95%) and sorbitol (yield ∼65%) in a microwave reactor with formic acid as the only hydrogen donor. We have established a unique relationship within Ru/triphenylphosphine that shows an important ligand effect, in contrast to, Ru/triphenylamine and Ru/catechol. The tailored electronic properties in Ru/phosphine were thoroughly examined by using state-of-the-art experimental techniques viz . EXAFS, XANES, XPS, DRIFTS and HAADF-STEM. The resulting phosphine-modified catalysts show a promotion in activity and selectivity towards less vulnerable aldehydes for hydrogenation, further confirmed by DFT calculations. This finding reveals a new protocol to tailor the activity of metal-single-atoms utilizing functional porous polymers as nanoreactors.